Increased bioavailability of cyclic guanylate monophosphate prevents retinal ganglion cell degeneration - Lauren K. Wareham; Ana C. Dordea; Grigorij Schleifer; Vincent Yao; Annabelle Batten; Fei Fei; Joseph Mertz; Meredith Gregory-Ksander; Louis R. Pasquale; Emmanuel S. Buys; Rebecca M. Sappington (Neurobiology of Disease, 2019)
The nitric oxide – guanylyl cyclase-1 – cyclic guanylate monophosphate (NO-GC-1–cGMP) pathway has emerged as a potential pathogenic mechanism for glaucoma, a common intraocular pressure (IOP)-related optic neuropathy characterized by the degeneration of retinal ganglion cells (RGCs) and their axons in the optic nerve. NO activates GC-1 to increase cGMP levels, which are lowered by cGMP-specific phosphodiesterase (PDE) activity. This pathway appears to play a role in both the regulation of IOP, where reduced cGMP levels in mice leads to elevated IOP and subsequent RGC degeneration. Here, we investigated whether potentiation of cGMP signaling could protect RGCs from glaucomatous degeneration. We administered the PDE5 inhibitor tadalafil orally (10 mg/kg/day) in murine models of two forms of glaucoma – primary open angle glaucoma (POAG; GC-1−/− mice) and primary angle-closure glaucoma (PACG; Microbead Occlusion Model) - and measured RGC viability at both the soma and axon level. To determine the direct effect of increased cGMP on RGCs in vitro, we treated axotomized whole retina and primary RGC cultures with the cGMP analogue 8-Br-cGMP. Tadalafil treatment increased plasma cGMP levels in both models, but did not alter IOP or mean arterial pressure. Nonetheless, tadalafil treatment prevented degeneration of RGC soma and axons in both disease models. Treatment of whole, axotomized retina and primary RGC cultures with 8-Br-cGMP markedly attenuated both necrotic and apoptotic cell death pathways in RGCs. Our findings suggest that enhancement of the NO-GC-1-cGMP pathway protects the RGC body and axon in murine models of POAG and PACG, and that enhanced signaling through this pathway may serve as a novel glaucoma treatment, acting independently of IOP.